BIOGEOCHEMICAL CHARACTERISTICS OF BIOMICROELEMENTS IN IRRIGATED SOILS - Akhmadjonov Avazbek Akmaljon ogli; Turdaliev Avazbek Turdalievich; Muhammadov Yakubjon Hamdamjon ogli (Innovate Conferences, 2025)
The article analyzes the bio microelement composition of irrigated meadow saz soils and light gray soils ( calcisols ) formed in the Fergana region and the cherry organs grown on them. The processes of migration and accumulation of biomicroelements in these soils and the cherry organs grown on them are also determined, biological absorption coefficients and geochemical spectra are developed.
Keywords: biomicroelement, biological absorption coefficient, biogeochemistry, geochemical spectrum, migration, accumulation.